ADAM10 correlates with uveal melanoma metastasis and promotes in vitro invasion. (11th September 2014) - Gangemi, Rosaria; Amaro, Adriana; Gino, Alice; Barisione, Gaia; Fabbi, Marina; Pfeffer, Ulrich; Brizzolara, Antonella; Queirolo, Paola; Salvi, Sandra; Boccardo, Simona; Gualco, Marina; Spagnolo, Francesco; et al.
Summary Uveal melanoma (UM) is a rare ocular tumor that may lead to deadly metastases in 50% of patients. A disintegrin and metalloproteinase (ADAM)10, ADAM17, and the HGF‐receptor c‐Met support invasiveness in different tumors. Here, we report that high ADAM10, MET, and, to a lesser extent, ADAM17 gene expression correlates with poor progression‐free survival in UM patients (hazard ratio 2.7, 2.6, and 1.9, respectively). About 60% of primary UM expresses c‐Met and/or ADAM10 proteins. Four UM cell lines display high levels of ADAM10 and ADAM17, which constitutively cleave c‐Met, inducing the release of soluble c‐Met. ADAM10/17 pharmacological inhibition or gene silencing reduces c‐Met shedding, but has limited impact on surface c‐Met, which is overexpressed. Importantly, ADAM10 silencing inhibits UM cell invasion driven by FCS or HGF, while ADAM17 silencing has a limited effect. Altogether our data indicate that ADAM10 has a pro‐invasive role and may contribute to UM progression.